The Effectiveness of Improved SIM Service Quality Through Smart SIM in the Bekasi City Police Area - Andhika Adjie Bahti Caesario (Police Studies Review, 2021)
SIM services in the city of Bekasi are still manual based so that in the manufacturing process there are still queues. And this also opens up opportunities for brokers' activities in carrying out their actions, both from the process of making and taking action against violations. In this study, the researcher used Effectiveness theory, public service theory, service quality theory, POAC (Planning, organizing, analyzing and controlling) and George R. Terry's 6m theories to become analytical tools. In analyzing this study using qualitative methods because researchers must obtain empirical data related to SIM services using smart SIMs in the city of Bekasi. And this research was also carried out with field research to get the real meaning of the situation and condition of the city of Bekasi. The results of the study found that the smart SIM program in the city of Bekasi was not effective because it did not meet internal and external factors, so that SIM services were still manual in the process of prosecuting violations and making SIMs. Facilities and infrastructure such as the smart SIM building, technical guidelines related to smart SIMs must exist so that this program can run properly to improve the quality of SIM services in the city of Bekasi.